2017
DOI: 10.7150/jca.20766
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling Reveals Novel Candidate Markers of Ovarian Carcinoma Intraperitoneal Metastasis

Abstract: Epithelial ovarian cancer (EOC) has the highest mortality among gynecological carcinomas. The lack of specific markers for prognostic determination of EOC progression hinders the search for novel effective therapies.The aim of the present study was (i) to explore differences in expressions of ATP-binding cassette (ABC) and solute carrier (SLC) transporter genes, genes associated with drug metabolism and cell cycle regulation between control ovarian tissues (n = 14), primary EOCs (n = 44) and intraperitoneal me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…This could be attributed to the nondirect relationships between these genes and features tested as well as the clinical differences between the two patient sets. Notably, these results support the conclusion of our previous studies, where especially the role of ABCA9, ABCA10, and ABCC9 transporters in OC progression and metastatic spread was stressed. Connection between high expression of ABC transporters from the subfamily A and poor outcome in serous OC was recently discussed in the study conducted by Hedditch et al Furthermore, the relatively small number of patients and the differences between clinical characteristics of both OC patient cohorts may be seen as limitations of the current study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This could be attributed to the nondirect relationships between these genes and features tested as well as the clinical differences between the two patient sets. Notably, these results support the conclusion of our previous studies, where especially the role of ABCA9, ABCA10, and ABCC9 transporters in OC progression and metastatic spread was stressed. Connection between high expression of ABC transporters from the subfamily A and poor outcome in serous OC was recently discussed in the study conducted by Hedditch et al Furthermore, the relatively small number of patients and the differences between clinical characteristics of both OC patient cohorts may be seen as limitations of the current study.…”
Section: Discussionsupporting
confidence: 91%
“…Verification of cDNA quality was performed by PCR amplification of ubiquitin C fragment. Before quantitative real‐time PCR, cDNA was preamplified; this step was described in detail in our previous works . qRT‐PCR was performed on Viia7 RT‐PCR System (Life Technologies, Carlsbad, CA, USA), with the use of TaqMan Gene Expression Assay (Life technologies) specific for each gene.…”
Section: Methodsmentioning
confidence: 99%
“… 24 However, to date, there is lack of sensitive molecular bio-markers for detecting early intraperitoneal metastasis. 28 Our findings show that KIF20A expression correlates strongly with intraperitoneal metastasis in EOC. Additionally, Cox regression analyses showed that intraperitoneal metastasis is an important factor that shortens the OS of EOC.…”
Section: Discussionmentioning
confidence: 51%
“…Therefore, KIF20A can been seen as a biomarker for detecting intraperitoneal metastasis at the early stages of EOC and may contribute to improving survival of EOC patients. 24 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…ABC transporters undertake the transport of various inflammatory mediators and lipids directly relevant to tumor progression in OC ( 4 ). Elsnerova et al ( 5 ) reported that the expression of ABCA7 was significantly higher in OC than in control ovarian tissue, and ABCA7 was upregulated in metastatic tumor tissue compared with primary OC. Additionally, increased expression of ABCA7 was significantly associated with poor outcomes in patients with OC ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%